Synthesis Of Dibenzofuran-1,3-Thiazole Carboxamide Derivatives And Screened For Anti-Inflammatory Potential - Shubham Singh; Dr. Arun Patel; Dr. Shailendra Patel (Revista Electronica de Veterinaria, 2024)
Objective: Synthesis of dibenzofuran-1,3-thiazole carboxamide derivatives and screened for anti-inflammatory potentialMaterial and methods: The goal of the current study was to synthesize a few dibenzofuran-1,3thiazolecarboxamide derivatives using four-step processes and several substituted benzylamines with the help of an appropriate catalyst. The following compounds were prepared: compound 1 (S-((4-chlorodibenzo[b,d]furan-1-yl)methyl) thiohydroxylamine), compound 2 (ethyl 2-(4 chlorodibenzo[b,d]furan-1-yl)-5-methylthiazole-4-carboxylate), compound 3 (2-(4-chlorodibenzo[b,d]furan-1-yl)-5 methylthiazole-4-carboxylic acid), and compound 4 (N-benzyl-2-(4-chlorodibenzo[b,d] furan-1-yl)-5-methyl thiazole 4-carboxamide). Compounds TC-1 through TC-14 are the codes for Compound 4. A total of twelve compounds have been created in these four processes, and the protein denaturation assay has been used to assess each compound's potential for reducing inflammation.Result and Discussion: The IR spectrum of the compounds has shown the characteristics peak (cm-1) of N-H at 3412; C=C-H at 3470; C=O at 1735; C=C at 1624–1446; C-N at 1015; p-substitution at 792; C-F at 1102; C-Cl at 855; C-Br at 1015; N-O at 1356; N=O at 1558. The 1HNMR spectra of Final compounds (TC-1 to TC-12) depicted the peak at 2.90 (3H, CH3); 4.64 - 4.65 (2H, CH2); 7.05-7.10 (2H, Ar-H); 7.35 (1H, Ar-H); 7.33 – 7.39 (4H, Ar-H); 7.45 (1H, Ar-H); 7.48 - 7.50 (1H, Ar-H); 7.62 - 7.63 (1H, Ar-H); 7.90 - 7.92 (1H, Ar-H); 8.38 – 8.40 (1H, N-H). Compound TC-1, mass spectrum has shown peak at m/z = 450.85, which matches the chemical formula C24H16ClFN2O2S. The protein denaturation assay of synthesized compound stated that most active compound are TC-1, TC-2, TC-3, TC-4 and TC-5 and compounds TC-7 & TC-9 has shown the mild activity and compound TC-6, TC-8, TC-10, TC-11 and TC-12 has shown modest activity.Conclusion: The substitution of fluoro, chloro, bromo, iodo, and nitro was one of the main groups that significantly increased the activity with para-substituent.